Error- and Tamper-Tolerant State Estimation for Discrete Event Systems under Cost Constraints - Li, Yuting; Hadjicostis, Christoforos N.; Wu, Naiqi; Li, Zhiwu (IEEE transactions on automatic control, 2023)
This paper deals with the state estimation problem in discrete-event systems modeled with nondeterministic finite automata, partially observed via a sensor measuring unit whose measurements (reported observed symbols) may be vitiated by a malicious attacker. The attacks considered in this paper include arbitrary deletions, insertions, or substitutions of observed symbols by taking into account a bounded number of attacks or, more generally, a total cost constraint (assuming that each deletion, insertion, or substitution bears a positive cost to the attacker). We provide a characterization of the sequences of symbols that match the received sequence of possibly corrupted symbols, and subsequently use them to recursively perform tamper-tolerant state estimation subject to cost constraints. Each step of the recursive state estimation procedure has complexity of O(|X||Σ |C) , where |X| ( |Σ | ) is the number of states (events) of the given finite automaton and C is the maximum total cost that is allowed for all deletions, insertions, and substitutions.